Genetic Variations of CD40 and LTβR Genes Are Associated With Increased Susceptibility and Clinical Outcome of Non-Small-Cell Carcinoma Patients - Dimitrakopoulos, Foteinos-Ioannis D.; Antonacopoulou, Anna G.; Kottorou, Anastasia E.; Kalofonou, Melpomeni; Panagopoulos, Nikolaos; Dougenis, Dimitrios; Makatsoris, Thomas; Tzelepi, Vasiliki; Koutras, Angelos; Kalofonos, Haralabos P. (Frontiers in Oncology, 2021)
Background Immune system-related receptors CD40 (tumor necrosis factor receptor superfamily member 5), BAFFR (tumor necrosis factor receptor superfamily member 13C), and LTβR (tumor necrosis factor receptor superfamily member 3) play a pivotal role in non-small-cell lung cancer (NSCLC). To further evaluate their role in NSCLC, CD40 rs1883832 (T>C), BAFFR rs7290134 (A>G), and LTβR rs10849448 (A>G) single-nucleotide polymorphisms (SNPs) were investigated regarding their impact in risk and clinical outcome of NSCLC patients. Methods The three selected SNPs were evaluated in 229 NSCLC patients and 299 healthy controls, while CD40, BAFFR, and LTβR protein expression was assessed by immunohistochemistry in 96 tumor specimens from NSCLC patients. Results In total, CD40 rs1883832 was associated with NSCLC risk, with the T allele, after adjusting for cofactors, being related to increased risk (p = 0.007; OR 1.701). Moreover, the CT genotype was associated with increased risk (p = 0.024; OR 1.606) and poorer 5-year overall survival (OS) after adjusting for cofactors (p = 0.001, HR 1.829), while CC was associated with higher CD40 expression in tumorous cells (p = 0.040) and in stromal cells (p = 0.036). In addition, AA homozygotes for the LTβR rs10849448 had increased risk for NSCLC in multivariate analysis (p = 0.008; OR, 2.106) and higher LTβR membranous expression (p = 0.035). Although BAFFR rs7290134 was associated with BAFFR membranous expression (p = 0.039), BAFFR rs7290134 was not associated with neither the disease risk nor the prognosis of NSCLC patients. Conclusions In conclusion, CD40 rs1883832 and LTβR rs10849448 seem to be associated with increased risk for NSCLC, while CD40 rs1883832 is also associated with OS of patients with NSCLC.